Bronhoskopija z upogljivim bronhoskopom - Triller, Nadja (Zdravniški vestnik, 2001)
Background. We were interested to study the effect of different ways of administering topical lidocaine and the possible benefit of using atropine as premedication for flexible bronchoscopy. Patients and methods. 105 patients were randomised into four groups. Lidocaine was administered either through the bronchoscope orby transcricoid injection. The use of atropine premedication was also randomised. The duration of bronchoscopy sessions, amount of lidocaine used, symptomes and signs such as coughing, heart rate andoxygene saturation were documented. Patients and medical staff graded theirperceptions of the procedure using a four-grade severity scale. Results. The duration of the bronchoscopy was not significantly prolonged in the group with bronchoscopic lidocaine administration compared to the transcricoid group(p - 0.6). The patients with bronchoscopic lidocaine administration required significantly more additional lidocaine than in the transcricoid group (p = 0.03). No significant difference was found in patients who receivedatropine and those without it. Severe coughing recorded by bronchoscopists and nurses was significantly more frequent in patients withoutatropine premedication (p = 0.006) but patient did not experience the bronchoscopy to be more unpleasant without atropine. Conclusions. Patients tolerated both variants of topical anaesthesia equally well but less amount ofadditional lidocaine was used by transcricoid administration. The use of atropine was of no benefit, but resulted in more tachycardia events.
Keywords: Anestezija lokalna; Anesthesia, local; Atropin; Atropine; bolezni dihal; Bronchoscopy; Bronhoskopija; diagnostika; dihala; Instrumentation; Lidocaine; Lidokain; lokalna anestezija; Methods